2022
DOI: 10.1007/s11356-022-25031-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of provincial carbon emission efficiency and analysis of influencing factors in China

Abstract: The massive use of energy has caused a rapid increase in global carbon dioxide emissions, resulting in a series of environmental problems such as climate warming. Investment in the energy industry can guide funds into green and clean production, reduce carbon emissions in the energy industry, and promote the green development of the energy industry. This paper considers the energy, the environment, the economy, and other factors and focuses on energy consumption and investment structure. Taking 30 provinces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…to optimize industrial structure. Different from the above conclusions, Sun and Dong [20] held industrial structure does not affect CEC.…”
Section: Studies On Cec and Its Influencing Factorscontrasting
confidence: 80%
“…to optimize industrial structure. Different from the above conclusions, Sun and Dong [20] held industrial structure does not affect CEC.…”
Section: Studies On Cec and Its Influencing Factorscontrasting
confidence: 80%
“…It is consistent with the benchmark regression's findings and demonstrates the benchmark regression's robustness. The output of building a dynamic panel model for differential GMM estimation is shown in Table 3 at (2). The first-order autocorrelation p-value is 0.01 and the second-order autocorrelation p-value is 0.20, which supports the notion that there is just a first-order autocorrelation and no second-order autocorrelation.…”
Section: Robustness Analysismentioning
confidence: 56%
“…Lin and Liu (2010) advocated the reduction of carbon emissions by maintaining GDP growth while controlling the urbanization rate and diminishing energy consumption intensity [1] . Sun et al (2016) highlighted the optimization of industrial and energy structures to enhance carbon emissions efficiency, with government intervention playing a pivotal role in achieving energy target constraints [2] . Wang et al (2018) revealed a significant inverted U-shaped curve relationship between economic growth and carbon emissions, while population agglomeration, technological advancements, openness to global markets, and intensified highway transportation together inhibit the increase in the level of urban carbon emissions [3] .…”
Section: Literature Review 21 Exploration Of Carbon Emissionsmentioning
confidence: 99%